3.5 MeV 양성자 조사에 의한 철(Fe)의 조사손상 영향 연구 - 채산; San Chae; 모신라피크; Mohsin Rafique; 김용수; Yong Soo Kim (대한금속·재료학회지, 54(1), 2016)
Radiation damage and its effects on Reactor Pressure Vessel (RPV) steel, an Iron (Fe) based alloy, have been important issues to assess the lifetime of nuclear power plants since nuclear reactor operation changed from an annual cycle to a high burn-up and extended cycle mode in the late 1990s. In this study, using an MC-50 accelerator, 99.99 % iron was irradiated with 3.5 MeV protons with doses in a range from 1x1010 to 1x1012 protons/cm2. First, the proton ion range was estimated at 45 μm using SRIM simulation; Optical Microscope (OM) observation results were in good agreement with the simulation. X-Ray Diffraction (XRD) analysis showed that the diffraction peak on the (110) plane, which is the most compact plane of the BCC structure, was intensified, probably due to the stress concentration stemming from the implanted proton atoms on the plane. Moreover, SEM results revealed that sputtered and recoiled iron atoms from the surface were deposited on the surface and that cracks developed and propagated at the sputtered spot.